2015
DOI: 10.1177/1753193415597096
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with improved outcomes following proximal row carpectomy: a long-term outcome study of 144 patients

Abstract: III, Prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
4
19
0
1
Order By: Relevance
“…1,2 In order to obtain rapid recovery, some authors prefer to combine PRC with posterior interosseous nerve (PIN) resection. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Review of the literature revealed several studies reporting the benefits of such combination (3)(4)(5). However, all of the studies on this subject were case series 1,3,[5][6][7][8][9][10][11] or studies comparing PRC and PIN neurectomy with other procedures, such as limited carpal fusions [12][13][14][15] capsule interposition arthroplasty, 16 or rehabilitation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In order to obtain rapid recovery, some authors prefer to combine PRC with posterior interosseous nerve (PIN) resection. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Review of the literature revealed several studies reporting the benefits of such combination (3)(4)(5). However, all of the studies on this subject were case series 1,3,[5][6][7][8][9][10][11] or studies comparing PRC and PIN neurectomy with other procedures, such as limited carpal fusions [12][13][14][15] capsule interposition arthroplasty, 16 or rehabilitation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, Wagner et al reported reduced pain, improved functional outcomes, and a higher rate of wrist joint preservation in patients with arthritis who underwent a proximal row carpectomy and a concomitant neurectomy procedure. 23 However, in our study, it may be argued that the PIN is denervated by performing the TWF itself.…”
Section: Discussionmentioning
confidence: 63%
“…Another long follow-up study of PRC for Kienb€ ock disease reported that 17 of 144 patients (12%) required revision surgery. 21 In our study, all patients were relieved from wrist pain and had no additional surgery, although the cohort did not include stage IV patients and had a smaller number of patients compared with the study of Croog and Stern. 20,21 Vascularized bone graft followed by CS with or without RS increased GS, reduced wrist pain, and enabled all patients to return to their jobs within 11 months after surgery.…”
Section: Discussionmentioning
confidence: 93%